Chadox1 Ncov-19 Vaccination: A Clinico-Pathological Review of Coagulation Derangement in Four Cases - Adekoya, A. O.; Adelekan-Popoola, F.; Fabamwo, A. O.; Abayomi, E. A.; Ajibare, A. O.; Odugbemi, B.; Soyemi, S. S. (British Journal of Healthcare and Medical Research, 2022)
BACKGROUND: Mass vaccination of the populace was one of the responses to mitigate the Severe Acute Respiratory Syndrome Coronavirus 2 (SARs CoV-2) pandemic. Some minor and major adverse effects have been reported. METHODS: This study reviewed the clinico-pathologic parameters of 4 patients with clinical and biochemical coagulation abnormalities following the administration of the Oxford AstraZeneca COVID-19 (ChAdOx1 nCoV-19) vaccination. Their clinical, laboratory and radiological parameters were retrieved and documented. RESULTS: All the patients had abnormality of coagulation with thrombus formation. Two of the reported patients had several risk factors for thrombosis and thus their diseases may not have causal relationship with the vaccination while the other 2 patients had no plausible clinical explanation for their coagulation abnormality. Mortality was recorded in two of the patients. CONCLUSION: Severe adverse effect of ChAdOx1 nCoV-19 Vaccination may not be rare. Physicians should have a high index of suspicion and there is also a need to upscale adverse events monitoring.